Chiral analysis of E‐ε‐viniferin enantiomers, towards a new chemotaxonomic marker of the vine. (22nd January 2023) - Gabaston, Julien; Buffeteau, Thierry; Irvine, Agnès Destrac; Gambetta, Gregory; Mérillon, Jean‐Michel; Waffo‐Téguo, Pierre
Abstract: BACKGROUND: The accurate characterization of grapevine cultivars ( Vitis vinifera ) is crucial for grape growers, winemakers, wine sellers, consumers and authorities, considering that mistakes could involve significant damage to the wine economic system. To avoid any misunderstanding, morphological, molecular and chemical tools are developed to positively identify grape varieties. RESULTS: E ‐ε‐viniferin is a stilbene dimer mainly present in the woody part of grapevine and present as a mixture of two enantiomers: ( 7aR, 8aR )‐(−)‐ E ‐ε‐viniferin (1 ) and ( 7aS, 8aS )‐(+)‐ E ‐ε‐viniferin (2 ). In addition to phenotypic and genotypic approaches, a chemotaxonomic method using E ‐ε‐viniferin enantiomers as chemical markers of grapevine cultivars was investigated. The isolation and purification of E ‐ε‐viniferin enantiomers by preparative high‐performance liquid chromatography (HPLC) and chiral HPLC from 14 red and eight white grapevine cane cultivars enabled us to determine the proportion of each enantiomer and therefore to calculate the enantiomeric excess for each variety. The relative abundance of each E ‐ε‐viniferin enantiomer permitted us to distinguish grape varieties, as well as to establish cultivar relationships and patterns through statistical analysis. CONCLUSION: This pioneering work highlighting the enantiomeric excess of E ‐ε‐viniferin as a chemical marker of grapevine paves the way for further studies to understand what mechanisms are involved in the production of these enantiomers in grapevine. © 2023 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.